Is a careers consultant for researchers a ‘third space’ professional in higher education? - Kate Murray (Journal of Learning Development in Higher Education)
In the limited research about the roles of careers professionals in higher education, very little has been written about careers consultants who specifically support academic researchers such as postgraduate research students and early career researchers, including postdoctoral research associates. This article sets out to create a better understanding of the role of careers consultants for researchers, drawing on the debate on ‘third space professionals’ to shed light on this complex and perhaps surprisingly challenging job in higher education institutions. After outlining a standard careers consultant’s work with reference to some of the available literature, the article uses a personal case study to highlight the realities of working across institutional boundaries. The author uses Daubney’s (2020) KASE framework drawn explicitly from careers work, work from Whitchurch (2013) from the third space literature, and a description from UKRI, the UK national funder, to describe and discuss their specific role (UKRI, cited Imperial, 2025). The article argues that, by performing many of the activities associated with an academic, the role-holder could be seen as an academic, but the author concludes that the notion of ‘third space professional’ fits well with the work of CCRs.